(3efXheI GdSjO eMeO HGbQ GdWHGHGFjs - (3GdWHGWHGFj, GdMLI, eMeO HGbQ Hf MSf, J (B1331 (3g`s
(3ChdgG (B:s
(3CMeO ef CfWbfj HMeOg (B... (3hHYO aGdTQja CqekG hCHG GdaGej ef Hfj WHGHG (B** (3jJdh Ydjc ef GdeNJGQ eVehf eG TGY ef GdCNHGQ (B** (3JaJQb GdCeI HYOeG VMi (B...s
(3BNQgG (B:s
... (3ef YGca Ydjg jheG hKHG jhe CHj YeG Edjg fOOG (B** (3agGc eG fedcg ef GOYG aj bHI eG NGH ajgG ef OYG (B** (3NJeJ fXej ajc hGdNJGes
(3JHUQI GdYfhGf (B:s
(3aj GdQO Ydi eG dabg GdZGFH` (B( (3TcQj CafOj GdHZOGOj (B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\49s
(3GdPQjYI (B14\2421s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds